2022
DOI: 10.1038/s42003-022-03358-0
|View full text |Cite
|
Sign up to set email alerts
|

Statistical parametrization of cell cytoskeleton reveals lung cancer cytoskeletal phenotype with partial EMT signature

Abstract: Epithelial–mesenchymal Transition (EMT) is a multi-step process that involves cytoskeletal rearrangement. Here, developing and using an image quantification tool, Statistical Parametrization of Cell Cytoskeleton (SPOCC), we have identified an intermediate EMT state with a specific cytoskeletal signature. We have been able to partition EMT into two steps: (1) initial formation of transverse arcs and dorsal stress fibers and (2) their subsequent conversion to ventral stress fibers with a concurrent alignment of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Through actin cytoskeletal remodeling, an increase in actin stress fiber formation and focal adhesion is important evidence of early EMT and is associated with increased cell migration ability . In particular, the formation and alignment of actin stress fibers form membrane protrusions and a specific cytoskeletal signature, which is also classified as a partial EMT phenotype. , The hybrid E/M phenotype is closely related to EMP. Hybrid E/M cells have both epithelial and mesenchymal characteristics and are mainly found after epithelial-derived cancer cells infiltrate blood vessels via EMT and convert to circulating tumor cells .…”
Section: Resultsmentioning
confidence: 99%
“…Through actin cytoskeletal remodeling, an increase in actin stress fiber formation and focal adhesion is important evidence of early EMT and is associated with increased cell migration ability . In particular, the formation and alignment of actin stress fibers form membrane protrusions and a specific cytoskeletal signature, which is also classified as a partial EMT phenotype. , The hybrid E/M phenotype is closely related to EMP. Hybrid E/M cells have both epithelial and mesenchymal characteristics and are mainly found after epithelial-derived cancer cells infiltrate blood vessels via EMT and convert to circulating tumor cells .…”
Section: Resultsmentioning
confidence: 99%
“…During EMT, when cell adhesion molecules are altered, the actin structure begins to reorganize and the cytoskeleton and shape change, so that the cells gain motility and invasion [ 29 ]. Actin is the key structural protein that forms the cytoskeleton of cells and plays a major role in functions including division, migration, and vesicular transport, participating in the coalescence and contraction of the cellular microfilament skeleton, and providing the impetus for cell migration [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cells expressed mesenchymal markers (SNAI1, VIM) while still retaining epithelial (CDH1) ones, exhibiting a partial EMT phenotype . Another study using image quantification to track EMT progression revealed a partial EMT phenotype with a unique cytoskeletal signature, consistent with decreased stiffness compared to mesenchymal cells . Tracking the morphological changes upon treatment with EMT-inducing growth factors has helped infer transition rates among different morphological cell states and has been used to develop classifiers to segregate epithelial vs mesenchymal states with 92% accuracy. Such characterization can be coupled with scRNA-seq data to extract information about E–M heterogeneity.…”
Section: Molecular and Functional Characterization Of Hybrid E/m Statesmentioning
confidence: 99%